Analisis Pelaksanaan Pembersihan Ruang Muat dan Pencegahan Penyumbatan Got Palka Untuk Melindungi Muatan Pada Kapal MV Curug Mas - Zainal Abidin; Kuncowati Kuncowati; Elva Febriana Anggraeny (Port Management and Maritime Administration Journal, 2026)
This study aims to analyze the implementation of cargo hold cleaning, the implementation of bilge well blockage prevention, as well as the causes of bilge well blockages and their impact on cargo aboard MV Curug Mas. This study employed a descriptive qualitative research method. Data were collected through observation, interviews, and documentation. The research informants consisted of the Chief Officer and Bosun. The results of the study indicate that cargo hold cleaning was carried out through the stages of preparation, cleaning implementation, and final inspection. However, several constraints were encountered during its implementation, resulting in the cleaning of the bilge well area and bilge well strainer not always being performed optimally. Bilge well blockages were generally caused by the accumulation of cargo residues, plastic waste, mud, dust, rust, and other foreign materials that obstructed the drainage system, potentially leading to water accumulation, increased cargo hold humidity, accelerated corrosion, and a higher risk of cargo damage. Therefore, cargo hold cleaning and bilge well maintenance should be carried out consistently and thoroughly to maintain the condition of the cargo hold and protect cargo throughout the voyage.